A Case of Significant Transaminitis with Liver Biopsy in a Pregnant Patient with COVID-19 - Dana Senderoff Berger; Anna Galyean; Kelvin Nguyen; Najeeb Alshak; Elizabeth Blumenthal (American Journal of Perinatology Reports, 2023)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2, has led to a global health crisis. The virus can cause varying severity of liver injury, but the mechanism has not yet been elucidated, especially in pregnancy.